2017
DOI: 10.1097/xce.0000000000000124
|View full text |Cite
|
Sign up to set email alerts
|

Effect of vitamin D status on lipid profile in premenopausal women: a cross-sectional study

Abstract: Objective High lipid levels play important roles in the pathogenesis of atherosclerosis and some authors suggest vitamin D deficiency as a risk factor for atherosclerosis. The aim of this study was to evaluate the effect of vitamin D status on lipid profile in premenopausal women. Patients and methods A total of 315 nonsmoking premenopausal female volunteers without diabetes mellitus were included in the study. Patients were divided into four subgroups. The groups were as follows: patients with less than or eq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 41 publications
1
2
0
Order By: Relevance
“…10 In this study, the deficiency of vitamin D was very high, these findings being compatible with the results of other studies. 11,12 The results showed a significant difference in the serum level of lipids with deficiency of vitamin D compared with sufficient vitamin D. These findings agree with the results of many other studies. [13][14][15] Also, the study showed that there was a significant negative correlation between the levels of cholesterol and vitamin D. The relation between hypercholesterolemia and vitamin D deficiency we found in this study may be attributed to the following: a defect in the cholesterol uptake may lead to the increase of its blood level due to a defect in the LDL receptors which leads to a reduction in the level of vitamin D at the same time because the LDL cholesterol is a precursor for vitamin D synthesis.…”
Section: Discussionsupporting
confidence: 89%
“…10 In this study, the deficiency of vitamin D was very high, these findings being compatible with the results of other studies. 11,12 The results showed a significant difference in the serum level of lipids with deficiency of vitamin D compared with sufficient vitamin D. These findings agree with the results of many other studies. [13][14][15] Also, the study showed that there was a significant negative correlation between the levels of cholesterol and vitamin D. The relation between hypercholesterolemia and vitamin D deficiency we found in this study may be attributed to the following: a defect in the cholesterol uptake may lead to the increase of its blood level due to a defect in the LDL receptors which leads to a reduction in the level of vitamin D at the same time because the LDL cholesterol is a precursor for vitamin D synthesis.…”
Section: Discussionsupporting
confidence: 89%
“…26,33,34 Furthermore, a negative association between the 25OHD level and the risk of CAD, including TG and LDL-C, has been suggested in healthy participants and patients. [33][34][35] In this respect, it has been demonstrated that people with normal serum 25OHD have a healthier lipid profile than those with VDD. Nonetheless, as mentioned previously, the association between 25HOD and women's lipid profiles remained unclear.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, the negative correlation noted between VDD and non-HDL in the current study is consistent with the results of some prior studies that assessed the atherogenic profile in obese females. 26,33,34 Furthermore, a negative association between the 25OHD level and the risk of CAD, including TG and LDL-C, has been suggested in healthy participants and patients. [33][34][35] In this respect, it has been demonstrated that people with normal serum 25OHD have a healthier lipid profile than those with VDD.…”
Section: Discussionmentioning
confidence: 99%